The Relationship Between Picky Eating And Stunting Incidents - Suyami Suyami; Setianingsih Setianingsih; Fitriana Noor Khayati; Istianna Nur Hidayati; Amanda Fauziah (An Idea Health Journal, 2026)
Stunting is a long-term nutrition problem that is still a major concern in Indonesia, especially during the first 1,000 days of a child's life. This study aims to find out the relationship between picky eating behavior and the occurrence of stunting in children aged 12 to 24 months at Puskesmas Polanharjo. The type of research is a quantitative analytical study with a case control design, involving 76 respondents in the stunting group. The sample size is 38 in each group. The sampling technique used is total sampling. The data was analyzed using the Chi-Square test. The results show a significant relationship between picky eating and stunting in children aged 12 to 24 months at Puskesmas Polanharjo, with a p-value of 0.005.